2011
DOI: 10.1136/bmj.d715
|View full text |Cite
|
Sign up to set email alerts
|

Peer support for patients with type 2 diabetes: cluster randomised controlled trial

Abstract: Objective To test the effectiveness of peer support for patients with type 2 diabetes. Design Cluster randomised controlled. Setting 20 general practices in the east of the Republic of Ireland. Participants 395 patients (192 in intervention group, 203 in control group) and 29 peer supporters with type 2 diabetes. Intervention All practices introduced a standardised diabetes care system. The peer support intervention ran over a two year period and contained four elements: the recruitment and training of peer su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
191
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(207 citation statements)
references
References 31 publications
12
191
0
4
Order By: Relevance
“…A recent study (30) with similar methodology assessed, for instance, the effect of peer support for patients with type 2 diabetes but could not show significant differences between groups in the improvement of the cardiovascular risk factors. In another study (31), patients with newly diagnosed type 2 diabetes received a 6-h structured group educational intervention, but no significant differences in the change in (16) 59 (12) 59 (13) 56 (10) ,0.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (30) with similar methodology assessed, for instance, the effect of peer support for patients with type 2 diabetes but could not show significant differences between groups in the improvement of the cardiovascular risk factors. In another study (31), patients with newly diagnosed type 2 diabetes received a 6-h structured group educational intervention, but no significant differences in the change in (16) 59 (12) 59 (13) 56 (10) ,0.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, an Irish trial of peer education to reduce CHD risk reported no benefit, but lacked a theoretical basis and required subjects to attend nine office-based didactic group sessions led by peers. 24 Our intervention was structured by the Theory of Planned Behavior and emphasized interactive role modeling, phone outreach, and practical, culturally appropriate tips. 25 In addition to peer support, African-American practice staff provided counseling with entertaining, culturally appropriate, educational slideshows and an interactive computer-based CHD tool.…”
Section: Discussionmentioning
confidence: 99%
“…The full details of the intervention components and the training received by peer supporters is reported elsewhere [10] and summarized in Box 1.…”
Section: Methodsmentioning
confidence: 99%
“…29 peer support groups were formed in the ten intervention practices. The primary outcomes of the trial (HbA1c, blood pressure, total cholesterol, and the Diabetes Well-being score) are reported elsewhere [10]. The peer supporters were trained to conduct nine group meetings in their general practice over a period of two years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation